Languages and nations : the Dravidian proof in colonial Madras - Trautmann, Thomas R. (Yoda Press, 2006)
"British rule of India brought together two very different traditions of scholarship on language, producing several intellectual breakthroughs of lasting value. Two of these breakthroughs were especially important: the conceptualization of the Indo-European language family by Sir William Jones at Calcutta in 1786 - proposing that Sanskrit is related to Persian and languages of Europe - and the conceptualization of the Dravidian language family of South India by F. W. Ellis at Madras in 1816 - the "Dravidian proof," showing that the languages of South India are related to one another but are not derived from Sanskrit. These concepts are valid still centuries later. In this book Thomas R. Trautmann continues the examination he began in Aryans and British Rule (1997). Whereas the previous book focused on Calcutta and Jones, the current volume examines these developments from the vantage of Madras, focusing on Ellis, Collector of Madras, and the Indian scholars with whom he worked at the College of Fort St. George. Making use of the rich colonial record, Trautmann concludes by showing how elements of the Indian analysis of language have been folded into historical linguistics and continue in the present as unseen but nevertheless living elements of modern theory."--BOOK JACKET.